2008
DOI: 10.1111/j.1542-474x.2007.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Premature Ventricular Complexes Originating from the Right Ventricular Outflow Tract Are Associated with Left Ventricular Dysfunction

Abstract: We demonstrated a significant association between frequent RVOT PVCs and LV dysfunction in patients without structural heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 14 publications
(20 reference statements)
5
98
0
1
Order By: Relevance
“…15) Some studies have reported that ablation of PVCs originating from the RV outflow tract resulted in reduction of the LV volume and improvement of the LV ejection fraction (LVEF). [16][17][18][19][20] The burden of PVCs has been reported to be correlated with the LVEF and known to be an independent predictive factor for worsening LV systolic function in patients with untreated frequent PVCs. 17,18,21) However, the burden of PVCs was not correlated with the volume of the cardiac chambers or the LVEF in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) Some studies have reported that ablation of PVCs originating from the RV outflow tract resulted in reduction of the LV volume and improvement of the LV ejection fraction (LVEF). [16][17][18][19][20] The burden of PVCs has been reported to be correlated with the LVEF and known to be an independent predictive factor for worsening LV systolic function in patients with untreated frequent PVCs. 17,18,21) However, the burden of PVCs was not correlated with the volume of the cardiac chambers or the LVEF in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] The burden of PVCs has been reported to be correlated with the LVEF and known to be an independent predictive factor for worsening LV systolic function in patients with untreated frequent PVCs. 17,18,21) However, the burden of PVCs was not correlated with the volume of the cardiac chambers or the LVEF in this study. The burden of PVCs can episodically increase or decrease without treatment, regardless of accompanying LV remodeling or LV systolic dysfunction, 7,21) which might explain the discrepant relationship between the burden of PVCs and LVEF in this study.…”
Section: Discussionmentioning
confidence: 99%
“…119 It is clear that the likelihood of TIC development increases with increasing PVC burden. However, what is also clear is that PVC burden is not the only contributing factor to impaired LV function.…”
Section: Ventricular Tachycardiamentioning
confidence: 99%
“…The abnormal pattern of electric activation and LV dyssynchrony may cause disruption and further progression of dyssynergic LV wall motion. [15][16][17] Here we introduce a novel method to develop a HF model, in which two ventricular leads were implanted in the right ventricle, connected to the pacemaker atrial and ventricular holes, excites the ventricle twice in one pacemaker beat and doubles the heart rate, using a proper coupling interval and basic heart rate, which is different from traditional rapid pacing. Extending the AV interval makes the ventricular rate as smooth as possible.…”
Section: Discussionmentioning
confidence: 99%